Multiple breath washout is feasible in the clinical setting and detects abnormal lung function in infants and young children with cystic fibrosis - Stahl, Mirjam; Joachim, Cornelia; Blessing, Kerstin; Hämmerling, Susanne Hedwig; Sommerburg, Olaf; Latzin, Philipp; Mall, Marcus A. (Respiration, 2014)
Background: Cystic fibrosis (CF) lung disease starts in the first months of life often before the onset of clinical symptoms. Multiple breath washout (MBW) detects abnormal lung function in infants and young children in the laboratory setting. Objective: The aim of this study was to determine the feasibility of MBW in 0- to 4-year-old children with CF and non-CF controls in the clinical setting. Methods: Fourteen children with CF (mean age 1.3 ± 1.0 years) and 26 age-matched non-CF controls were sedated with chloral hydrate and MBW was performed with sulfur hexafluoride. Results: MBW measurements were successful in 27 of 40 children (67.5%). The mean lung clearance index (LCI) was significantly higher in CF patients compared to non-CF controls (p = 0.006). Further, the frequency of elevated LCI (z-score >1.96) was significantly increased in CF patients compared to controls (p = 0.0003). Conclusions: We conclude that MBW is feasible and sensitive to detect abnormal lung function in infants and young children with CF in the clinical setting.
Gesehen am 02.09.2020